Should we believe? The fictional, the virtual and the real in the contemporary novel. Issue 2 (1st February 2020) - Wilson, Leigh
ABSTRACT: Recent work from both novelists and literary critics has suggested that the contemporary novel is sick of fiction and has turned instead to the 'real'. This article questions this understanding of the contemporary novel and, by focusing in particular on the 6-volume Min Kamp by Karl Ove Knausgaard, suggests instead that the most important representational model for the contemporary novel is the virtual. In establishing this, the article returns to both a history of the concept of the virtual and to Coleridge's 'willing suspension of disbelief' in order to make visible the role of the virtual as a model for contemporary prose fiction.